Value of Travel Social Media Influencers (TSMI) and their Relationship with Trust in Branded Posts Based on the Perspective of Gen Z in Hanoi, Vietnam - Hoang Thi Thu, Huong; Huyen, Le Thi Thu; Linh, Hoang Phuong; Linh, Nguyen Ha; Minh, Tran Quang; Ngoan, Do Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 1 No 3, 2021)
The emergence and development of Travel Social Media Influencers – TSMI has become a new social media channel for people who work in the field of tourism, bringing destination brands closer to travelers, especially generation Z. According to the recent survey of 800 zoomers living in Hanoi, the results show that 7 factors representing TSMI value have been newly adjusted. In addition, generation Z’s trust in branded posts is influenced by 4 aspects that represent TSMI, namely (1) Communication and interaction methods; (2) Level of pervasiveness; (3) Degree of identification; and (4) Similarity and familiarity with influence level. However, generation Z’s trust is not affected by the other 3 groups of factors including, (1) Charisma and trustworthiness; (2) Informational value; and (3) Professionalism in tourism. In order to implement branded posts effectively based on TSMI, the research results are especially significant in proposing measures so as to attract generation Z tourists in Hanoi.